Open Universities: Innovative Past, Challenging Present, and Prospective Future - Sarah Guri-Rosenblit (Athabasca University Press, 2019)
This article examines the innovative past of the large-scale, single-mode open universities that follow the model of the UK Open University (UKOU), analyzes the main challenges which they are currently facing in the digital era, and concludes with highlighting leading prospects for their future operation.